2023
DOI: 10.1111/asj.13876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rumen microbiota transfaunation on the growth, rumen fermentation, and microbial community of early separated Japanese Black cattle

Shuhei Takizawa,
Takumi Shinkai,
Kunihiko Saito
et al.

Abstract: This study aimed to investigate the effect of rumen microbiota transfaunation on the growth, rumen fermentation, and the microbial community of Japanese Black cattle that were separated early from their dams. Here, 24 calves were separated from their dams immediately after calving, 12 of which were transfaunated via inoculation with rumen fluid from adult cattle at the age of 2 months while the remaining 12 were kept unfaunated (not‐inoculated). Feed efficiency monitoring was performed during 7–10 months of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Previous research, such as the work by Chiquette et al [38], demonstrated that the introduction of Prevotella bryantii 25A into the rumen of dairy cows via a rumen fistula led to increased butyrate levels. Similarly, Takizawa et al [39] found that microbiota translocation in Japanese black cattle resulted in a higher abundance of Prevotellaceae_UCG-004, subsequently elevating acetate and butyrate levels. This was further supported by Zhao et al [40], who confirmed through in vitro fermentation tests that Prevotellaceae_UCG-001 contributes to lignocellulose degradation and elevates VFA concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…Previous research, such as the work by Chiquette et al [38], demonstrated that the introduction of Prevotella bryantii 25A into the rumen of dairy cows via a rumen fistula led to increased butyrate levels. Similarly, Takizawa et al [39] found that microbiota translocation in Japanese black cattle resulted in a higher abundance of Prevotellaceae_UCG-004, subsequently elevating acetate and butyrate levels. This was further supported by Zhao et al [40], who confirmed through in vitro fermentation tests that Prevotellaceae_UCG-001 contributes to lignocellulose degradation and elevates VFA concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple factors contribute to the variation in rumen microbiota, and breed per se significantly impacts the composition of cattle ruminal microbiota 9 11 . Recently, there has been ongoing analysis of the rumen microbiome in Japanese Black cattle 12 , 13 , but discussions have mainly focused on the relationship between rumen fermentation characteristics and microorganisms. Moreover, blood metabolites originate from the metabolites produced by rumen microbes; therefore, analyzing the connection between the rumen microorganisms influencing rumen fermentation and the blood metabolites reflecting the outcomes of rumen fermentation would be useful.…”
Section: Introductionmentioning
confidence: 99%